Pemanfaatan MOODLE pada Pembelajaran Online Mata Kuliah Aplikasi Komputer Mahasiswa Fakultas Dakwah dan Komunikasi IAIN Antasari - Surya Eka Priyatna (Alhadharah: Jurnal Ilmu Dakwah, 2014)
Efficiency and effectiveness in the lecture now is the demand that must be met. It is directly proportional to the advancement of technology growing so rapidly. With the construction of the Internet network infrastructure on Puskom IAIN Antasari then it is possible to use the internet for the development of effective learning methods to students. The research was conducted on students of the Faculty of Da'wa and Communication IAIN Antasari Banjarmasin. In the Computer Applications course, in addition to running the course face to face, as a companion also held online learning using Moodle as an application Learning Management System (LMS).